Thiol suppression of human immunodeficiency virus type 1 replication in primary cord blood monocyte-derived macrophages in vitro. - Lioy, J (1993)
We investigated the effects of glutathione (GSH), the major naturally occurring thiol, and a pharmacologic thiol precursor of GSH, N-acetyl cysteine (NAC), on the expression of human immunodeficiency type 1 (HIV-1) in primary cord blood and adult donor monocyte-derived macrophages (MDM). HIV-1 infection of cord blood and adult MDM was accomplished after incubating 10-15-d-old cultures for 4 h with a monocyte-tropic strain of HIV-1 (Bal). After 1 wk in culture cell supernatants were tested for reverse transcriptase (RT) activity. MDM were exposed to 5, 10 and 20 mM concentrations of both GSH and NAC before infection, during infection, and after infection was established. GSH and NAC suppressed the replication of HIV-1 in both primary cord blood and adult donor MDM in a concentration dependent fashion. These suppressive effects were more pronounced in cord-derived cells than in adult-derived cells. In cells treated with GSH or NAC before infection, there was no significant rise in RT activity as compared with controls. Similarly, when cells were treated with GSH and NAC and simultaneously infected, there was also no significant rise in RT activity after 1 wk in culture. In cells treated after infection was established, RT values were suppressed 80-90% that of untreated controls. This effect persisted for 1-2 wk after exposure to GSH and NAC. Untreated controls demonstrated syncytium formation and lost characteristics of spreading and elongation 2 wk after HIV-1 infection, whereas most of the treated cells remained free of syncytium and retained cytoplasmic spreading, adherence, and elongation. These data are consistent with other studies of thiol suppression of HIV-1 replication and demonstrate a similar observation for primary cultured cord MDM. These results may offer new approaches toward cellular protection after infection with HIV-1.